Understanding the Concepts and Physiologic Principles of Lymphatic Microsurgery - Sosin, Michael; Yin, Christine; Poysophon, Poysophon; Patel, Ketan M. (Journal of Reconstructive Microsurgery, 2016)
Surgical techniques such as lymphaticovenous anastomosis and vascularized lymph node (VLN) transfer are gaining momentum in the treatment of lymphedema. Although surgeons may be technically capable of performing these complex procedures, understanding the normal physiology of the lymphatic system and the pathophysiology of lymphedema is critical to the patient selection process, determining which specific procedure to perform, considering the specific anatomic location of surgery, and optimization of outcomes. To familiarize the plastic surgeon with the pathophysiological principles of lymphatic surgery for lymphedema, this review focuses on lymphatic anatomy, histology, physiology, disease progression, and staging in the context of lymphaticovenous anastomosis and VLN transfer.
Keywords: lymphedema; lymphatic surgery; microsurgery; lymphaticovenous; vascularized lymph node transfer